A systematic review of DDH screening practices in the UK - Nicholas Birkett; Edward Karam; David Ferguson; Deepika Pinto; Claudia Maizen (Exploration of Musculoskeletal Diseases, 2024)
Background: The United Kingdom (UK) currently employs a selective screening system for developmental dysplasia of the hip (DDH). Despite this, late presentation rates remain high. The aim of this study was to systematically review the available literature to gain an understanding of screening practices throughout the UK. Methods: A systematic review was conducted. Studies reporting DDH screening methods from the UK were included. The primary outcome measure was the method of ultrasound and clinical screening. Secondary outcomes were the treatment rate and late presentation rate. A narrative analysis was undertaken, as meta-analysis was felt to be inappropriate due to the differences between included studies. Results: Nine studies were eligible and included. There was significant variability in practice, with a variety of ultrasound techniques being used and a variety of staff members performing clinical screening. Treatment rate ranged from 16.4/1,000 to 0.8/1,000. Late presentation rate ranged from 1.28/1,000 to 0.27/1,000. Discussion: In spite of a national consensus statement, there is no standardised approach to clinical or ultrasound screening in the UK. A variety of different methods are used, which may explain the persistently high late presentation rate. A national system of quality control and a standardised screening process is recommended, with specialised training in the Graf method of ultrasound.